Analisis Nilai Nilai Tradisi Pernikahan Ngambik Bini Pada Masyarakat Suku “Dayak Desa” Di Desa Sungai Pukat Kecamatan Kelam Permai Kabupaten Sintang - Finny Aprillia Christy Pagye; Iwan Ramadhan; Muhammad Nur Imanulyaqin; Hadi Wiyono; Patrisia Rahayu Utami (Indo Publishing, 2026)
This research aims to analyze the Ngambik bini marriage tradition among the Dayak Desa indigenous community in Sungai Pukat Village, Kelam Permai Sub-District, Sintang Regency. The study employs a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation. The findings reveal that the Ngambik bini ceremony consists of preparation, core implementation, and closing stages, all conducted in accordance with customary rules. Each stage embodies social, moral, spiritual, and aesthetic values collectively understood by the community. Gestures such as communal prayer, respectful postures, and silat movements carry social meanings as they are witnessed and interpreted together. Symbols including tawak , ngumbak, stone, rice, egg, water, isau, and flintlock rifle convey messages of steadfastness, protection, responsibility, togetherness, and cultural identity. By uncovering the meanings embedded in each stage and symbol, this research contributes to strengthening understanding of local cultural values as part of the Dayak Desa community's identity. It also supports the preservation of the Ngambik bini tradition through scientific documentation and serves as a reference for future studies on symbolic interactions, cultural values, and local customs.